Big Data Analytics and market competitiveness of selected firms in Lagos State, Nigeria - Chike, Nwosu Kanayo; Mbamalu, Euphemia Ifunanya; Oguanobi, Chimezie Alex; Egbunike, Chinedu Francis (goodwood publishing, 2023)
Purpose: This study specifically evaluates the effect of Intangible Big Data Analytics Resources (IBDAR) and Tangible Big Data Analytics Resources (TBDAR) on a firm’s market competitiveness in manufacturing firms. The authors used RBV as the main theoretical framework to investigate this. Research methodology: This study used a survey research design. The study employed a non-probability sample and a final sample of seventy-two employees selected from manufacturing firms in Lagos State, Nigeria. Results: The hypotheses were tested using multiple linear regressions. The empirical results showed that the organizational use of TBDAR has a significant effect on Market Competitiveness (MCOM), and that the organizational use of IBDAR has a significant effect on MCOM. Limitations: First, the sample is restricted to only the Nigerian setting; to draw broader and deeper implications, it could be useful to take diverse samples from different contexts and sectors. Second, this study does not utilize the PLS-SEM technique to model mediators and moderators. Contribution: This study has significant policy implications for practitioners and is an original study based on primary data from Nigerian manufacturing firms.